Analisis Kelengkapan Pengisian Formulir Informed Consent Pada Pasien Rawat Inap Di RS Pusat Pertamina - Jonathan Wicaksono; Sustin Farlinda; Thomas M. Purba Purba (Indonesian Journal Publisher, 2022)
The completeness of filling out the informed consent form at Pertamina Central Hospital Jakarta is still less than the Hospital Minimum Service Standard, which is 100%. This is based on the researcher's preliminary study that the completeness of filling out the informed consent form at Pertamina Central Hospital Jakarta was recorded at 73%, while the remaining 27% were incomplete. The purpose of this study was to review the completeness of filling out the informed consent form at Pertamina Central Hospital. This research uses quantitative research with descriptive approach method. Data collection was carried out by observing and documenting the informed consent form as well as interviews with medical record officers. The results showed that the analysis component with the highest completeness was 98%, namely the patient's/guardian's name and patient's signature, while the analysis component with the lowest completeness was 38%, namely the signatures and names of witnesses I and II. The cause of the incomplete informed consent form is the lack of explanation and emphasis by PPA officers on the patient or patient's family to fill out and complete the data that is part of it to be filled and completed.